DNA polymerase delta interacting protein 3 facilitates the activation and maintenance of DNA damage checkpoint in response to replication stress - Sufang Zhang; Ernest Y. C. Lee; Marietta Y. W. T. Lee; Dong Zhang (Animal Models and Experimental Medicine, 2022)
Abstract Background Replication stress response is crucial for the maintenance of a stable genome. POLDIP3 (DNA polymerase delta interacting protein 3) was initially identified as one of the DNA polymerase δ (Pol δ) interacting proteins almost 20 years ago. Using a variety of in vitro biochemical assays, we previously established that POLDIP3 is a key regulator of the enzymatic activity of Pol δ. However, the in vivo function of POLDIP3 in DNA replication and DNA damage response has been elusive. Methods We first generated POLDIP3 knockout (KO) cells using the CRISPR/Cas9 technology. We then investigated its biological functions in vivo using a variety of biochemical and cell biology assays. Results We showed that although the POLDIP3‐KO cells manifest no pronounced defect in global DNA synthesis under nonstress conditions, they are sensitive to a variety of replication fork blockers. Intriguingly, we found that POLDIP3 plays a crucial role in the activation and maintenance of the DNA damage checkpoint in response to exogenous as well as endogenous replication stress. Conclusion Our results indicate that when the DNA replication fork is blocked, POLDIP3 can be recruited to the stalled replication fork and functions to bridge the early DNA damage checkpoint response and the later replication fork repair/restart.